Tricyclic cell-penetrating peptides for efficient delivery of functional antibodies into cancer cells - Tietz, O; Cortezon Tamarit, F; Chalk, R; Able, S; Vallis, K (Springer Nature, 2022)
The intracellular environment hosts a large number of cancer- and other disease-relevant human proteins. Targeting these with internalized antibodies would allow therapeutic modulation of hitherto undruggable pathways, such as those mediated by protein–protein interactions. However, one of the major obstacles in intracellular targeting is the entrapment of biomacromolecules in the endosome. Here we report an approach to delivering antibodies and antibody fragments into the cytosol and nucleus of cells using trimeric cell-penetrating peptides (CPPs). Four trimers, based on linear and cyclic sequences of the archetypal CPP Tat, are significantly more potent than monomers and can be tuned to function by direct interaction with the plasma membrane or escape from vesicle-like bodies. These studies identify a tricyclic Tat construct that enables intracellular delivery of functional immunoglobulin-G antibodies and Fab fragments that bind intracellular targets in the cytosol and nuclei of live cells at effective concentrations as low as 1 μM.